Development of femoral component design geometry by using DMROVAS (design method requiring optimum volume and safety). Issue 2 (12th August 2019) - Öztürk, Burak; Erzincanli, Fehmi
Abstract : Purpose: This study aims to design a femoral component with minimum volume and maximum safety coefficient. Total knee prosthesis is a well-established therapy in arthroplasty applications. And in particular, with respect to damaged or weakened cartilage, new prostheses are being manufactured from bio-materials which are compatible with the human body to replace these damages. A new universal method (design method requiring optimum volume and safety [DMROVAS]) was propounded to find the optimum design parameters of tibial component. Design/methodology/approach: The design montage was analyzed via the finite element method (FEM). To ensure the stability of the prosthesis, the maximum stress angle and magnitude of the force on the knee were taken into consideration. In the analysis process, results revealed two different maximum stress areas which were supported by case reports in the literature. Variations of maximum stress, safety factor and weight were revealed by FEM analysis, and ANOVA was used to determine the F force percentage for each of the design parameters. Findings: Optimal design parameter levels were chosen for the individual's minimum weight. Stress maps were constructed to optimize design choices that enabled further enhancement of the design models. The safety factor variation (SFV) of 5.73 was obtained for the volume of 39, 219 mL for a region which had maximum stress. At the same time, for a maximum SFV and at the same time an average weight, values of 37, 308 mL and 5.8 for volume and SFV were attained, respectively, using statistical methods. Originality/value: This proposed optimal design development method is new and one that can be used for many biomechanical products and universal industrial designs.